Collective properties of Petitella georgiae in tube environments - Shuang Gu; Quan Quan (Scientific Reports)
Abstract The movement of biological swarms is widespread in nature, and collective behavior enhances a swarm’s adaptability to its environment. However, most research focuses on free swarm movement, overlooking the impact of environmental constraints such as tubes. This study examines the swimming behavior of Petitella georgiae through a tube. Observations of position, speed, and direction reveal that each fish is influenced by the swarm’s distribution in its field of view. The speed ratio between the middle region and edge region positively correlates with tube angles, and higher speeds are associated with higher densities within specific angle ranges.